Persistent congestion, renal dysfunction and inflammatory cytokines in acute heart failure: a prognosis study. Issue 7 (July 2020) - Pugliese, Nicola R.; Fabiani, Iacopo; Conte, Lorenzo; Nesti, Lorenzo; Masi, Stefano; Natali, Andrea; Colombo, Paolo C.; Pedrinelli, Roberto; Dini, Frank L.
Abstract : Aims: Chronic kidney dysfunction (CKD) and persistent congestion influence heart failure prognosis, but little is known about the role of inflammation in this association. We assessed the relationship between inflammatory biomarkers, persistent congestion and CKD and their prognostic implications in patients with acute heart failure. Methods: We enrolled 97 hospitalised patients (mean age: 66 ± 12 years, ejection fraction: 30 ± 8%) with acute heart failure. Before discharge, congestion was assessed using a heart failure scoring system on the basis of Framingham criteria. Circulating levels of high-sensitivity C-reactive protein, TGF-β-1, IL-1, IL-6, IL-10, TNF-α, soluble tumour necrosis factor receptor type 1 and 2 were measured. Patients were divided into four groups according to the presence of CKD (estimated glomerular filtration rate <60 ml/min/1.73 m 2 ) and congestion (Framingham heart failure score ≥2). The primary end point was the combination of death and rehospitalisation for acute heart failure. Results: During a median follow-up of 32 months, 37 patients died and 14 were rehospitalised for acute heart failure. Patients with CKD and congestion had significantly higher TNF-α ( P  = 0.037), soluble tumour necrosis factor receptor type 1 ( P  = 0.0042) and soluble tumour necrosis factor receptor type 2 ( P  = 0.001), lower TGF-β-1 ( P  = 0.02) levels, and the worst outcome ( P  < 0.0001). Congestion ( P  = 0.01) and CKD ( P  = 0.02) were independent predictors of the end-point together with N-terminal prohormone of brain natriuretic peptide ( P  = 0.002) and TNF-α ( P  = 0.004). TNF-α attenuated the direct relation between CKD, congestion and outcome, explaining 40% of the difference in the outcome. Conclusion: In patients hospitalised with acute heart failure, the prognostic impact of persistent congestion and CKD is associated with increased cytokine levels, which may also interfere with the outcome. Abstract : Supplemental Digital Content is available in the text